ACTUAL PROBLEMS OF ABDOMINAL PATHOLOGY IN CHILDREN (ACCORDING MATERIALS OF CONGRESS OF RUSSIAN PEDIATRISTS, 2008) - E.A. Kornienko; S.I. Erdes; E.L. Igumenova (Вопросы современной педиатрии, 2009)
This article describes actual problems of abdominal pathology in children: irritable colon syndrome and constipation. The questions of forming those state, criteria and standards of diagnostics and treatment, questions of differential diagnostics are discussed. This article presents modern recommendations on treatment of irritable colon syndrome and constipation, including medicamental and other methods of treatment.Key words: children, irritable colon syndrome, constipation, diagnostics, treatment.(Voprosy sovremennoi pediatrii — Current Pediatrics. 2009;8(2):68-76)